2015
DOI: 10.1155/2015/721938
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Short-Term Outcomes after Postisometric Muscle Relaxation or Kinesio Taping Application for Normalization of the Upper Trapezius Muscle Tone and the Pain Relief: A Preliminary Study

Abstract: The main purpose of the study was to evaluate the resting bioelectrical activity of the upper trapezius muscle (the UT muscle) before and after one of the two interventions: postisometric muscle relaxation (PIR) and Kinesio Taping (KT). Moreover a comparison between group results was conducted. From the initial 61 volunteers, 52 were selected after exclusion criteria and were allocated randomly to 2 groups: PIR group and KT group. Outcome measures were assessed at baseline and completion of the intervention. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
1
11
0
1
Order By: Relevance
“…Hong et al reported significant increase of PPT after SAS [14] whereas Martín-Pinta do Zugasti et al found no change in PPT as well [15]. For PIR, a reduction of VAS by 0.7 has been reported by Ptaszkowski et al [12]. As mentioned earlier we considered a change of 2.0 or more in VAS as clinically relevant for this study.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…Hong et al reported significant increase of PPT after SAS [14] whereas Martín-Pinta do Zugasti et al found no change in PPT as well [15]. For PIR, a reduction of VAS by 0.7 has been reported by Ptaszkowski et al [12]. As mentioned earlier we considered a change of 2.0 or more in VAS as clinically relevant for this study.…”
mentioning
confidence: 65%
“…Postisometric relaxation therapy (PIR) was first described by Karel Lewit [10] and is believed to be effective for trigger point treatment [1,11]. A recent study compared PIR with Kinesio Taping and found the latter more effective for pain reduction [12]. A muscle energy technique, descriebed very similar to PIR, was as effective as ischaemic compression to reduce trigger point pain [13].…”
Section: Purpose ▼mentioning
confidence: 99%
See 1 more Smart Citation
“…When the kinesiology tape was applied to athletes with scapular dyskinesis, upper trapezius activity decreased, and scapular kinematics, such as scapular posterior tilt and upward rotation, improved [21]. Application of the kinesiology tape to the upper trapezius was more effective in pain relief than postisometric muscle relaxation intervention [22]. Furthermore, when it was applied to the pelvis of patients with low back pain having sacroiliac joint dysfunction and an increased sacral horizontal angle, the pelvic anterior tilt and pain were reduced [23].…”
Section: Introductionmentioning
confidence: 93%
“…There were twenty RCTs related to the cervical spine that assessed KT, with overall PEDro scores ranging from 4 to 8 (Appendix 2 File: Appendix 2I). Ten RCTs pertained to mechanical or non-specific neck pain [161][162][163][164][165][166][167][168][169][170], nine RCTs pertained to trigger points or pain of the upper trapezius [171][172][173][174][175][176][177][178][179], and one RCT investigated whiplash associated neck pain [180]. There were no RCTs that studied rigid taping, Mulligan taping or Mc-T in relation to conditions of the cervical spine.…”
Section: Cervical Spinementioning
confidence: 99%